the answer to the question using slope and y-intercept
(2,3) and (4,5)
Tutors, please sign in to answer this question.
You could also use point-slope form to solve for your equation.
m = (y1-y2)/(x1-x2)
m = (3-5)/(2-4) = (-2)/(-2) = 1
y - y1 = m(x - x1)
y - 3 = 1(x - 2)
y - 3 = x - 2
Add 3 to both sides to isolate y - leaving you with the form y = mx+b
y = x + 1
Using this method saves you the step or finding b and then writing your equation. You're done when you have y = _____.
y = mx + b
m = (5-3)/(4-2) = 1
thus, y = x + b
plus x =2, y =3 into the equation, we get: 3 = 2+b
we can get b = 1
the solution is y = x+1